Reducing Regional Poverty Gaps Through Optimized Local Government Spending - Rah Adi Fahmi Ginanjar; Mahdani Mahdani; Muhammad Alifian Nuriman; Zoraya Alfathin Rangkuti; Saharuddin Didu; Tony Santika Chendrawan (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
This study aims to analyze the relationship between local government expenditure allocation and poverty reduction and map the time needed to fade the disparity between the dichotomy of regions. The methods used statistical approaches and mathematical models, both linear and non-linear, to project the time of inequality fading by observing all districts and cities in Banten Province during the period 2005-2024. The study also examines the differences in spending patterns between North and South Banten in the context of fiscal decentralization. Key results show that spending on these functions has a strong negative correlation with poverty rates, while predictive models show optimistic and pessimistic scenarios in the fading of inequality. This study concludes that optimizing local government spending can significantly accelerate the reduction of poverty gaps. The contribution of this research provides a theoretical and practical basis for more effective fiscal policies in supporting inclusive and sustainable development.